Reimagining Education For Sustainable Futures: Integrating Local Wisdom And Global Citizenship In Curriculum Design - Adityawarman (Journal of Global Educational Perspectives, 2025)
In the era of global educational transformation, the integration of local wisdom and global citizenship education (GCE) emerges as a strategic response to the challenge of creating sustainable learning environments. This study aims to reimagine curriculum design by embedding indigenous cultural values into global sustainability competencies, thereby shaping learners who are locally rooted yet globally responsible. Employing a qualitative descriptive approach, this research explores curriculum models, teaching practices, and teacher perceptions across selected schools in Indonesia’s coastal and island regions, where local wisdom plays a vital role in community life. Data were collected through document analysis, interviews, and classroom observations, followed by thematic analysis to identify intersections between local culture and global educational goals. The findings reveal that integrating local wisdom into GCE fosters a transformative learning experience, encouraging empathy, ecological awareness, and collective responsibility among students. However, challenges persist in aligning traditional knowledge systems with standardized curriculum frameworks, highlighting the need for flexible, context-responsive educational policies. This study contributes to the global discourse on Education for Sustainable Development (ESD) by offering a hybrid curricular model that harmonizes cultural identity and global competency. The proposed framework emphasizes the importance of recontextualizing education not merely as a vehicle of knowledge transmission but as a moral and ecological endeavor towards sustainable futures.